All-MXene (2D titanium carbide) solid-state microsupercapacitors for on-chip energy storage. Issue 9 (10th August 2016) - Peng, You-Yu; Akuzum, Bilen; Kurra, Narendra; Zhao, Meng-Qiang; Alhabeb, Mohamed; Anasori, Babak; Kumbur, Emin Caglan; Alshareef, Husam N.; Ger, Ming-Der; Gogotsi, Yury
Abstract : Novel, noble-metal-free, solid-state all-titanium carbide (Ti3 C2 T x ) MXene microsupercapacitors are fabricated, which exhibit high areal capacitance, excellent rate-capability, and are transferable to any surface. Abstract : On-chip energy storage is a rapidly evolving research topic, opening doors for the integration of batteries and supercapacitors at the microscale on rigid and flexible platforms. Recently, a new class of two-dimensional (2D) transition metal carbides and nitrides (so-called MXenes) has shown great promise in electrochemical energy storage applications. Here, we report the fabrication of all-MXene (Ti3 C2 T x ) solid-state interdigital microsupercapacitors by employing a solution spray-coating method, followed by a photoresist-free direct laser cutting method. Our prototype devices consisted of two layers of Ti3 C2 T x with two different flake sizes. The bottom layer was stacked large-size MXene flakes (lateral dimensions of 3–6 μm) serving mainly as current collectors. The top layer was made of small-size MXene flakes (∼1 μm) with a large number of defects and edges as the electroactive layer responsible for energy storage. Compared to Ti3 C2 T x micro-supercapacitors with platinum current collectors, the all-MXene devices exhibited a much lower contact resistance, higher capacitances and better rate-capabilities. Areal and volumetric capacitances of ∼27 mF cm −2 and ∼357 F cm −3, respectively, at a scan rate of 20 mV s −1 were achieved. The devices also demonstrated excellent cyclic stability, with 100% capacitance retention after 10 000 cycles at a scan rate of 50 mV s −1 . This study opens up a plethora of possible designs for high-performance on-chip devices employing different chemistries, flake sizes and morphologies of MXenes and their heterostructures.